Critical success factors toward a safe city as perceived by selected medium enterprises in the province of Nueva Ecija: A crafted business development policy model - Santos, Angelo Reyes (Asian Development Policy Review, 2023)
The purpose of this study is to further characterize and evaluate the important success criteria of a safe city for medium-sized businesses in Nueva Ecija in the Philippines, which will be used for the business development policy model. A descriptive method was employed to collect quantitative data. In order to determine or estimate the degree to which the values for the variables are related or vary in a discernible pattern, the descriptive design is an appropriate method for enabling the collection of accurate and trustworthy data through survey measurement of two or more variables. Purposeful sampling, also known as judgment, selective, or subjective sampling is used. This is a sampling strategy in which researchers utilize their own judgment when selecting members of a population to participate in a study. A group of 100 owners of mid-sized businesses in Nueva Ecija served as the study’s respondents. Other initiatives outside of Nueva Ecija are also included in this report. The Critical Success Factor (CSF) Model was created and served as the foundation for the questionnaire. The research indicates that the city government and the LGU effectively promote objectives, guidelines, safety, and security. Cities are evolving into smarter places using new technologies for monitoring, analyzing, and planning to increase efficiency and quality of life. Coordination between government and stakeholders is necessary to foster smart cities, and robust economies drive the adoption of safer city programs. The research recommends continuous development of law enforcement, new integrated systems, and recovery assistance after business emergencies. Additionally, the research suggests continuing to develop a long-term program for public space enhancement that integrates crime prevention, designs inclusive public spaces, implements traffic safety campaigns, and promotes safer driving practices.